Deskripsi Kemampuan Pemecahan Masalah Matematika Siswa Ditinjau Dari Tingkat Kecerdasan Logis Matematis - Nur Hasmira (Tautologi: Journal of Mathematics Education, 2023)
This research includes qualitative research, which discusses students' problem solving abilities in terms of the level of logical mathematical intelligence that is still very limited. This study aims to describe and determine the factors that influence students' mathematical problem solving abilities in terms of the level of mathematical logical intelligence in comparative material. This research was conducted in class VIII.2 UPTD SMPN 1 Parepare. Collecting data using research instruments in the form of test sheets and interview guidelines. The analysis of problem solving abilities produced in this study is indicated to be able to meet the indicators of problem solving abilities and indicators of mathematical logical intelligence. The subjects in this study were 3 people based on the results of the answer sheets, namely 1 student with a high level of logical mathematical intelligence, 1 student with a moderate level of mathematical logical intelligence and 1 student with a low level of mathematical logical intelligence. The results of the study show that students with a high level of logical mathematical intelligence are able to understand problems, are able to formulate resolution plans, are able to carry out problem solving and are able to re-examine solutions, students with moderate levels of logical mathematical intelligence are able to understand problems but are not complete, are able to develop plans for completion, are able to carry out the settlement, able to re-examine but lacking in drawing conclusions, subjects with low levels of logical mathematical intelligence have not been able to apply every indicator of problem solving ability. And the factors that affect problem solving ability in terms of logical mathematical intelligence level are students who are less careful in solving problems and the lack of teachers in providing varied or non-routine examples of questions.